The Correlation Between Active Smoking Behaviour and SYNTAX Score on Male Patients with Coronary Artery Disease - Maringka, Kezia Michella Yusak; Ermawan, Romi; Sari, Dian Puspita; Rahmat, Basuki (Universitas Airlangga, 2026)
Background: This study aimed to determine the relationship between smoking behavior and SYNTAX score in male patients with coronary artery disease (CAD) at the Regional General Hospital of NTB Province. Material and Methods: This observational analytic study used a cross-sectional approach, conducted from August to November 2023 in the cath lab of NTB Provincial General Hospital. A total of 94 male CAD patients diagnosed through coronary angiography were enrolled, divided into smokers and non-smokers. Medical records were reviewed, and SYNTAX scores were calculated using angiography data under the supervision of a consultant cardiologist. The study used consecutive sampling to select eligible patients based on the inclusion and exclusion criteria. Data were analyzed using independent t-tests and ANCOVA. Results: Among the 94 patients in this study, 48.9% had a history of hypertension, 25.5% had DM, and 31.9% had dyslipidemia. The mean age was 57.9 years with a standard deviation of 9.7. The body mass index (BMI) ranged from 18.4 to 34.8, with 39.4% in the normal BMI category. Regarding therapy history, 2.1% had received statin and antiplatelet therapy before angiography. SYNTAX score distribution showed that 57.4% had a low SYNTAX score, 23% had an intermediate score, and 17% had a high score, with a mean of 20.7 ± 11.9. After adjusting for confounding variables, a significant association was found between smoking behavior and SYNTAX score (p = 0.046; mean difference = 4.8). Conclusion: There is a significant difference in SYNTAX score between male CAD patients with smoking behavior and without smoking behavior. Smoking behavior is significantly associated with higher SYNTAX scores. Smoking cessation interventions may help reduce the complexity of CAD. Further research is needed to evaluate the impact of smoking cessation on SYNTAX scores in this population. – Highlights: 1. This study demonstrates that smoking is linked to more severe and complex coronary artery disease, as reflected by higher angiographic severity scores in male patients. 2. Even after accounting for major cardiovascular risk factors, smoking remains an independent contributor to disease burden, reinforcing its critical role in worsening coronary pathology.